2021
DOI: 10.3390/s21237875
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Over-Ground Robot-Assisted Gait Training for Children with Ataxic Cerebral Palsy: A Case Report

Abstract: Poor balance and ataxic gait are major impediments to independent living in ataxic cerebral palsy (CP). Robot assisted-gait training (RAGT) has been shown to improve the postural balance and gait function in children with CP. However, there is no report on the application of RAGT for children with ataxic CP. Here, we report two cases of children with ataxic CP who underwent over-ground RAGT along with conventional therapy for 4 weeks. Outcome measures including the gross motor function measure (GMFM), pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Core stability training improved strength and endurance of muscles, trunk control, corrective postural control mechanisms, and ability to use the vestibular, somatosensory, and visual systems to maintain balance and stability 9 Lee et al (2021) Republic of Korea [ 27 ] Single‐subject experimental study CYP; n = 1 Cerebellar ataxia Physiotherapy Exercise and function Problem-based task training consisting of four walking tasks- a 10‐step walk and return, walking while carrying an object, walking between parallel lines, and kicking a ball (10 min/task, 8 sessions each in baseline and intervention phase followed by 1-year follow-up. Total duration of intervention phase not reported) Repeated practice of functional tasks led to improvement in balance and physical performance thereby improving overall motor function in children with cerebellar ataxia 10 Yoo et al (2021) Republic of Korea [ 36 ] Case Report CYP; n = 2 Ataxic CP Physiotherapy Exercise and function Over-ground robot assisted gait training (Angel Legs M20) alongside conventional physical and occupational therapy (5 sessions/week for 1 month) Improvements reported in postural control, functional mobility, and balance in children with ataxic CP. Improvements observed after RAGT in areas of gross motor function that did not improve with conventional therapy alone 11 Maring et al (2013) USA [ 42 ] Descriptive mixed method study Parents; n = 30 Friedreich ataxia Physiotherapy Exercise and function Semi-structured interviews of parents of children with FA to understand perceived effectiveness and barriers to PT 67% of children received PT intervention, most commonly muscle strengthening and stretching (considered increasingly useful as the child gets older), following by balance training (minimally helpful) Hydrotherapy was the most frequently recommended intervention by parents Muscle stretching HEP considered challenging and burdensome (9% reported consistent use) External barriers: lack of expert providers Internal barriers: Limited time and energy, lack of awareness and children’s preference 12 Harris-Love et al (2004) USA [ ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Core stability training improved strength and endurance of muscles, trunk control, corrective postural control mechanisms, and ability to use the vestibular, somatosensory, and visual systems to maintain balance and stability 9 Lee et al (2021) Republic of Korea [ 27 ] Single‐subject experimental study CYP; n = 1 Cerebellar ataxia Physiotherapy Exercise and function Problem-based task training consisting of four walking tasks- a 10‐step walk and return, walking while carrying an object, walking between parallel lines, and kicking a ball (10 min/task, 8 sessions each in baseline and intervention phase followed by 1-year follow-up. Total duration of intervention phase not reported) Repeated practice of functional tasks led to improvement in balance and physical performance thereby improving overall motor function in children with cerebellar ataxia 10 Yoo et al (2021) Republic of Korea [ 36 ] Case Report CYP; n = 2 Ataxic CP Physiotherapy Exercise and function Over-ground robot assisted gait training (Angel Legs M20) alongside conventional physical and occupational therapy (5 sessions/week for 1 month) Improvements reported in postural control, functional mobility, and balance in children with ataxic CP. Improvements observed after RAGT in areas of gross motor function that did not improve with conventional therapy alone 11 Maring et al (2013) USA [ 42 ] Descriptive mixed method study Parents; n = 30 Friedreich ataxia Physiotherapy Exercise and function Semi-structured interviews of parents of children with FA to understand perceived effectiveness and barriers to PT 67% of children received PT intervention, most commonly muscle strengthening and stretching (considered increasingly useful as the child gets older), following by balance training (minimally helpful) Hydrotherapy was the most frequently recommended intervention by parents Muscle stretching HEP considered challenging and burdensome (9% reported consistent use) External barriers: lack of expert providers Internal barriers: Limited time and energy, lack of awareness and children’s preference 12 Harris-Love et al (2004) USA [ ...…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, RAGT in combination with conventional physical and occupational therapy led to improvements in postural control, functional mobility, and balance in children with ataxic cerebral palsy. Improvements observed after RAGT in areas of gross motor function that did not improve with conventional therapy alone support the potential benefits of over-ground RAGT on gross motor function in these children [36]. A conference proceeding from 2014 reported significant improvement from a dynamic movement orthosis suit and orthotic shoes in gait and stability for a 12-year-old girl with severe ataxia [23].…”
Section: Exercise and Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…(minimal assistance)] of children with severe cerebellar ataxia who had posterior fossa hemorrhage [3] . Yoo et al ( 2021) also reported that robot-assisted gait training improved balance, walking capacity, and GMFM of children with ataxic cerebral palsy who had cerebellar atrophy [27] . On the other hand, taskoriented reaching activities, stretching, strengthening, and gait training resulted in a decrease in the rate of falls, while a decline in the gait speed of children with Friedreich ataxia [28] .…”
Section: Exercise For Ataxia Balance Gross Motor Skills and Adl Abilitymentioning
confidence: 99%